Concentration-Dependent Inhibitory Effect of Baicalin on the Plasma Protein Binding and Metabolism of Chlorzoxazone, a CYP2E1 Probe Substrate, in Rats In Vitro and In Vivo - Gao, Na (Public Library of Science, 2013)
Some of the components found in herbs may be inhibitors or inducers of cytochrome P450 enzymes, which may therefore result in undesired herb-drug interactions. As a component extracted from Radix Scutellariae, the direct effect of baicalin on cytochrome P450 has not been investigated sufficiently. In this study, we investigated concentration-dependent inhibitory effect of baicalin on the plasma protein binding and metabolism of chlorzoxazone (CZN), a model CYP2E1 probe substrate, in rats in vitro and in vivo. Animal experiment was a randomized, three-period crossover design. Significant changes in pharmacokinetic parameters of CZN such as C(max), t(1/2) and V(d) were observed after treatment with baicalin in vivo (P<0.05). C(max) decreased by 25% and 33%, whereas t(1/2) increased by 34% and 53%, V(d) increased by 37% and 50% in 225 mg/kg and 450 mg/kg baicalin-treated rats, respectively. The AUC and CL of CZN were not affected (P>0.05). Correlation analysis showed that the changes in CZN concentrations and baicalin concentrations were in good correlation (r>0.99). In vitro experiments, baicalin decreased the formation of 6-OH-chlorzoxazone in a concentration-dependent manner and exhibited a competitive inhibition in rat liver microsomes, with a Ki value of 145.8 µM. The values of C(max)/Ki were 20 and 39 after treatment with baicalin (225 and 450 mg/kg), respectively. Protein binding experiments in vivo showed that the plasma free-fraction (fu) of CZN increased 2.6-fold immediately after baicalin treatment (450 mg/kg) and in vitro showed that baicalin (125–2500 mg/L) increased the unbound CZN from 1.63% to 3.58%. The results indicate that pharmacokinetic changes in CZN are induced by inhibitory effect of baicalin on the plasma protein binding of CZN and CYP2E1 activity.